Evaluating Dispersion of Residential CO and NOx Emissions with the Help of Different Models in Körfez District, Kocaeli Province - Kazım Demirarslan; Şenay Çetin Doğruparmak (Doğal Afetler ve Çevre Dergisi)
This study was conducted to investigate the dispersion of spatial source CO and NOx emissions with the help of different models in Korfez District, Kocaeli Province. Emissions from residential areas were chosen as the spatial source in the region and residents were divided into four different sections. The residential area is 5.31 km2 and natural gas, fuel-oil, wood, and coal are used as heating fuels in this district. With the help of the obtained data, emission rates were calculated using the mass-based emission factors of U.S. Environmental Protection Agency. These ratios were divided into residential areas and data were obtained in g/s.m2 and these data were entered to AERMOD, ISCST-3 and CALPUFF VIEW programs for the purpose of modelling. As a result of the modelling study, daily and annual dispersion maps were obtained. When the maps were examined, with AERMOD, the daily maximum concentrations of CO and NO were estimated to be 651,27 μg/m3, 18,29 μg/m3 while the annual concentrations were found as 128,47 μg/m3 and 2,90 μg/m3, respectively. The obtained daily maximum CO and NOx values with the help of ISCST-3 program were as 290,29 μg/m3 and 11,77 μg/m3 and the maximum annual values were as 86,48 μg/m3 and 1,95 μg/m3, respectively. The values of CO and NOx emissions obtained with the help of CALPUFF modelling program were as 692,67 µg/m3 and 15,64 µg/m3 , respectively, on daily basis and as 124,08 µg/m3 and 4,53 µg/m3 respectively, on annual basis. While there seemed to be a similarity in all three programs for CO when considering dispersion directions on the distribution maps, it was pointed out that the concentrations dispersed in the direction of east and west of Korfez district on AERMOD and CALPUFF maps as this dispersion was towards to the west of the county on ISCST-3 map. On NOx distribution maps, the residential areas of Korfez district were observed as the locations of density for NOx. The concentration propagation directions were same for all three programs particularly for annual dispersions maps and the concentration levels at receiver points in these directions were also determined as equal.